Cationic micelles self-assembled from quaternized cellulose-g-oligo (ε-caprolactone) amphiphilic copolymers. (October 2019) - Liu, Suzhen; Zhang, Li; Chen, Xiaohong; Chu, Tingting; Guo, Yanzhu; Niu, Meihong
Graphical abstract: Highlights: Cationic amphiphilic cellulose polymer was synthesized via ROP reaction. QC- g -OCL could self-assemble into spherical micelles with core-shell structure. The surface of micelles was cationic charged. Self-assemble behavior of QC- g -OCL was correlated with its hydrophobic/hydrophilic group contents. Abstract: A novel kind of cationic cellulose- g -oligo(ε-caprolactone) amphiphilic polymer (QC- g -OCL) was obtained by homogeneous ring-opening polymerization of ε-caprolactone (ε-CL) from quaternized cellulose (QC) in 1-butyl-3-methylimidazolium chloride (BmimCl) ionic liquids. Chemical structures and properties of the copolymers were characterized by FT-IR, 1 H NMR, 13 C NMR, XRD and TGA techniques. The grafting ratios of OCL chain onto QC- g -OCL were adjusted by changing the molar ratio of CL to QC. The micelles self-assembled from QC- g -OCL were prepared by ultrasonic-assisted dissolution method, and comprehensively analyzed by dynamic light scattering (DLS), TEM and fluorescence spectroscopy techniques. The micelles were in spherical shape with average hydrodynamic radiuses (Rh ) in the range of 170–237 nm. Moreover, their critical micelle concentration (CMC) values were decreased from 0.302 mg/mL to 0.089 mg/mL with increasing the degree substitution values of OCL (DSOCL ) from 0.16 to 0.60. The ζ-potentials of micelles in water were ranged from 37.2 mV to 48.3 mV, indicating that the shells of micelles were constituted by ationic quaternary ammonium group. All of these findings established that the cationic cellulose-based micelles would be a promising aqueous carrier for hydrophobic drug.